GMS transport sector strategy 2030 toward a seamless, efficient, reliable, and sustainable GMS transport system. (Metro Manila, Philippines Asian Development Bank, 2018)
This new strategy for transport development in the Greater Mekong Subregion (GMS) consists of a strategic framework covering 20182030 and a set of performance indicators initially covering 20182022.It is mainly a strategic document providing a common framework for GMS cooperation in the transport sector. Cooperation in the transport sector has been at the core of the GMS Economic Cooperation Program since its inception in 1992. The main thrust of the program was eliminating the barriers to cooperation, and the significant lack of connectivity was a critical constraint on economic relations among the GMS countries.
Keywords: Transportation -- Asia -- Planning; Sustainable transportation; Electronic books